2017
DOI: 10.5271/sjweh.3691
|View full text |Cite
|
Sign up to set email alerts
|

A health economic outcome evaluation of an internet-based mobile-supported stress management intervention for employees

Abstract: A health economic outcome evaluation of an internet-based mobile-supported stress management intervention for employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 57 publications
0
56
1
Order By: Relevance
“…As no previous health economic evaluations of ICBT for patients diagnosed with stress-related disorders have been conducted, to our knowledge, there are no available cost-effectiveness estimates of the target population with which we can directly compare our results. Nevertheless, 2 recently published studies evaluated cost-effectiveness of ICBT for employees with elevated levels of stress, 1 from an employer’s perspective (including only costs relevant for the employer, ie, presenteeism, absenteeism, and treatment costs) [24] and 1 adopting a full societal perspective [25]. Results of these studies were similar to those found in this study, with probabilities of treatment cost-effectiveness of approximately 70% compared with WLC at a WTP of US $0 [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As no previous health economic evaluations of ICBT for patients diagnosed with stress-related disorders have been conducted, to our knowledge, there are no available cost-effectiveness estimates of the target population with which we can directly compare our results. Nevertheless, 2 recently published studies evaluated cost-effectiveness of ICBT for employees with elevated levels of stress, 1 from an employer’s perspective (including only costs relevant for the employer, ie, presenteeism, absenteeism, and treatment costs) [24] and 1 adopting a full societal perspective [25]. Results of these studies were similar to those found in this study, with probabilities of treatment cost-effectiveness of approximately 70% compared with WLC at a WTP of US $0 [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 2 recently published studies evaluated cost-effectiveness of ICBT for employees with elevated levels of stress, 1 from an employer’s perspective (including only costs relevant for the employer, ie, presenteeism, absenteeism, and treatment costs) [24] and 1 adopting a full societal perspective [25]. Results of these studies were similar to those found in this study, with probabilities of treatment cost-effectiveness of approximately 70% compared with WLC at a WTP of US $0 [24,25]. In these studies, as in ours, costs because of presenteeism were large and constituted central cost drivers in the cost-effectiveness analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TiC-P has been proven to be a feasible and reliable instrument for measuring healthcare utilization and productivity loss (55). The German adaption has been utilized in a substantial number of randomized controlled trials as a basis for health economic outcome evaluations (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67).…”
Section: Costs Associated With Psychiatric Illnessmentioning
confidence: 99%